Perlindungan Hukum Peralihan Kepemilikan Hak Atas Satuan Rumah Susun Terkait Perbuatan Melawan Hukum dalam Proses Jual Beli Tanpa Akta Jual Beli: (Studi Kasus Putusan Nomor :182/Pdt.G/2023/PN.Jkt.Tim) - Muhammad Exel Bagus Nugroho; Arsin Lukman; Rury Octaviani (CV Rewang Rencang, 2025)
Increasing space in open areas is one way to counteract the negative impact of housing and urbanization on land use. Apart from being a way to live, housing and settlements are more appropriately understood as a process of human settlement. Apart from being a practical place to live, housing and settlements are also the process of human settlement. The construction of flats aims to meet the needs of decent housing for the people, by increasing the usability and yield of land use in densely populated areas and only a limited land area is available. The definition of flats varies, flats are also called Flats/Apartments/Condominiums. In this study, there are two problem formulations. First, how to protect the owner of a flat unit in the case of a transfer of ownership carried out without a sale and purchase deed. Second, what is the role of the court in resolving disputes over the transfer of ownership of apartment units carried out without a sale and purchase deed based on Decision No.182/Pdt.G/2023/PN.Jkt.Tim. The research method used in this study is normative juridical which uses secondary data sources or data obtained from literature materials. From this study, it can be concluded that there are acts of unlawful acts that are demanded with compensation for losses. So that the role of the court in granting the lawsuit in its relevance to the Registration of Transfer of Land Rights can be the basis for being able to register the process of reversing the name of the certificate to the National Land Office as a substitute for the Deed of Sale and Purchase from PPAT.